PENGARUH PENAMBAHAN MINYAK KELAPA MURNI (VIRGIN COCONUT OIL/VCO) TERHADAP PENAMPILAN PRODUKSI AYAM BROILER FASE FINISHER - Paskalis Robinson (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2017)
This study concerns the Effect of Addition of virgin coconut oil on Production performance at the Boiler Finisher Phase. The study was conducted on March 10 to April 5, 2017, at Kampung Kaliharapan Nabire District, Papua Province. This research was designed using Randomized Complete Design with four treatments and each treatment got 5 repetitions so that 20 units of the experiment were obtained, each the experiment unit consisted of 3 (three) chickens. The tested treatment is giving of various doses of pure coconut oil mixed with drinking water that is: Without pure coconut oil as control, 5cc / 100 dose chicken, Dosage 10 cc / 100 chicken, and Dosage 15 cc / 100 head/ chicken. The observed variable is Weight gain (gr / head / day), feed consumption (gr / head / day) and Feed conversion (FCR). The data were analyzed experimentally if there was any difference it would be carried out the further test with Duncan Multiple Test. The results of the study showed that all treatments treated with VCO could increase the body weight of chicken broiler, ie, increase significantly occurred from week V to VII, more efficient in consuming feed and the higher the doses given the lower the feed conversion rate. From the results of this study, it can be concluded that the addition of VCO has a significant effect on the increase of body weight and the decrease of the feed conversion rate at broiler Finisher phase. The higher given dose tends to increase body weight and decrease the feed conversion rate. The best or more efficient VCO dosage for finisher phase of broiler chicken is 15 cc / 100.